Understanding media debate around migration: the relation between favorable and unfavorable representations of migration in the Greek Cypriot Press - Kadianaki, Irini; Avraamidou, Maria; Ioannou, Maria; Panagiotou, Elisavet (My University, 2018)
Continuous and increasing worldwide migration has sparked an intense social debate in multiple forums. Media play a key role in constructing, monitoring, and framing this debate. This study focuses on a qualitative analysis of the media debate around migration in Cyprus via (a) studying how migrants are represented in the Greek Cypriot Press and (b) assessing the extent and the way in which favorable and unfavorable representations around migration are in dialogue. Toward this end, thematic and dialogical analyses were conducted on articles published in 4 daily Greek Cypriot newspapers between 2011 and 2015. Findings showed that migrants were constructed in economic (e.g., as assets to economy) and humanitarian (e.g., as victims) terms in the favorable representations, whereas in the unfavorable ones, migrants were constructed primarily as a threat to the local economy, to security, and to the nation's culture and existence. In terms of the relation between the 2, favorable representations engaged more clearly and in more detail with alternative representations of migrants than unfavorable ones. Favorable representations focused more on countering negative representations of migrants while unfavorable representations focused more on countering negative representations of the authors (e.g., being racist), through disclaimers. Nevertheless, authors of favorable representations managed alternatives by stigmatizing those who held opposing views and did not elaborate on their arguments. These findings speak to the superficial and polarizing character of the debate and point to implications for further research on the relation between the different stances on migration in other forums such as social media and TV.
Keywords: Cyprus; Debate; Media; Migration; Representations